History of ideas on woman - Agonito, Rosemary (Putnam, 1977)
Bibliography: p. 403 - 414; Thirty discourses and treatises on the subject of women, by influential thinkers ranging from Plato, Aristotle, and Augustine to Freud, Beauvoir, and Friedan, are accompanied by critical analyses